Color Atlas of Pediatric Anatomy, Laparoscopy, and Thoracoscopy - McHoney, Merrill; Kiely, Edward M.; Mushtaq, Imran (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This atlas of anatomy and operative techniques provides a thorough outline of the procedures commonly used in laparoscopic and thoracoscopic pediatric surgery. Step-by-step operative photographs are accompanied by explanatory text, and line diagrams are used to highlight the important anatomy as seen endoscopically. Alternative techniques, instruments, and steps are described when appropriate, and attention is drawn to highlights and pitfalls. While each chapter includes some basic background on the condition in question, the focus is very much on the operative procedures. Color Atlas of Pediatric Anatomy, Laparoscopy, and Thoracoscopy is ideal for those establishing a laparoscopic practice as well as for those in training who wish to embark on minimally invasive surgery. It also serves as a supplementary atlas of anatomy and surgical technique for younger surgeons and medical students. .
Keywords: Medicine.; Human anatomy.; Abdominal surgery.; Minimally invasive surgery.; Pediatric surgery.; Thoracic surgery.; elektronické knihy; electronic books